Polar constituents, biological effects and nutritional value of Sideritis sipylea Boiss - Tomou, Ekaterina Michaela; Lytra, Krystalia; Chrysargyris, Antonios; Christofi, Maria Dolores; Miltiadous, Panagiota; Corongiu, Gian Luca; Tziouvelis, Marinos; Tzortzakis, Nikos G.; Skaltsa, Helen (My University, 2021)
The present study focuses on the polar constituents and biological effects of the methanol extract and the infusion of wild Sideritis sipylea Boiss. from Samos island (Greece), as well as on the nutritional and mineral contents of this plant. The total phenolic content and antioxidant activity were examined. In addition, the anti-acetylcholinesterase property was evaluated, revealing strictly lower results than the control, galanthamine. Furthermore, the nutritional value of the plant is reported herein for the first time, revealing a promising source of protein. To the best of our knowledge, this study is the first work on the infusion of this species and the nutritional value of the plant.
Keywords: Wild Sideritis sipylea; Anti-acetylcholinesterase; Antioxidant; Cytotoxicity; Mineral content; Nutritional value